Designing with z-pins : locally reinforced composite structures - Lander, James K. (Cranfield University, 2008)
This thesis describes specific new applications of Z-Fibre ® pinning and focuses the attention onto the failure modes of locally reinforced (z-pinned) structures. Design implications of the use of localised reinforcement on structures, rather than laboratory coupons, are considered. Z-pinning reinforcement is applied to cylindrical crash tubes and I-section patch joints manufactured from woven carbon / epoxy pre-pregs. Z-pinning is shown to improve the Specific Energy Absorption (SEA) of the crash tubes by up to 76 %, the exact amount depending on the tube geometry. For the I-section patch joints, an initial increase in ultimate load carrying capability due to z-pin use is observed and, as the quantity of z- pins increases, a change in failure mode is induced. Z-pinning is also shown to enhance the damage tolerance of these. The ability to predict major changes to the structural response due to use of z-pins, and design for them accordingly, is the next step in the understanding of the technology. The design element of this study is contained in the development of a new Finite Element model using cohesive interface elements. The provision of mode II input data for this model comes from End Loaded Split (ELS) testing of the woven laminates and continued development of the Z-shear test. A new analysis for quantifying the crack sliding displacement, based on the ELS test, is developed. Z-shear testing has shown that the z-pin ‘mode II’ fracture energy is strongly affected by the amount of mode I opening of the shear surfaces. Here, new data are obtained for a fully constrained, pure mode II case. Using this modelling tool, changes in failure mode due to z-pin use can be predicted. Verification is provided by a new simulation of the I-section patch joint geometry.